Body Mass Index (BMI) and Waist Circumference Levels of Belly Dance Participants at Purnama Studio - Nur Latifah; Perdinanto; Akhmad Amirudin (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the Body Mass Index (BMI) levels and waist circumference of Belly Dance participants at Sanggar Purnama. This research employed a descriptive quantitative method using a total sampling technique, involving 15 active Belly Dance participants. The instruments used included BMI measurements and waist circumference. The results showed that most participants (40%) fell into the obesity category I, 26.67% were overweight, 26.67% were in the normal range, and 6.67% were classified as obesity category II. Regarding waist circumference, 53% of participants were within the normal range, while 47% exceeded the normal threshold for women (>80 cm), indicating central obesity. These findings suggest that although Belly Dance is regularly practiced, not all participants achieved ideal body weight or waist circumference. This highlights the importance of a holistic approach to weight management, incorporating regular physical activity, a balanced diet, and a healthy lifestyle. This study contributes to the understanding of Belly Dance’s effectiveness on body composition and participant health and serves as a foundation for future health intervention strategies.